SOME NOTES ON THE BOND YIELD PROBLEM. - Snyder, Ralph W. (The Accounting Review, 1952)
In a recent article accountant Hugh K. Stelson found the yield on a bond by use of a modified or improved correction formula, apparently published only a few years ago. The new formula is an extension of the long-known Newton's formula for finding the root of an equation by successive corrections to progressively closer. First point, The initial trial rate should meet two standards: it should be as close as possible to the true rate, and it should be a tabular rate, so that the labor of computing can be avoided. If a bond table is also available, use of the formula is still easier. The table should have a rate interval no larger than half percent. The benefits of an initial error no larger than .000625 lie not so much in the digits "625" as in the three zeros. For there is a rule of thumb for Newton's formula in one of his texts on the theory of equations to the effect that if h begins with k zeros, the computation should be carried to 2k decimal places. The foregoing discussion is applicable to short-term bonds, up to say 30 or 40 periods.